ANALISIS PERILAKU PENGGUNA SISTEM INFORMASI PENGELOLAAN NILAI RAPOR MENGGUNAKAN METODE UTAUT - Megawati Megawati; Wanda Afita (LPPM Universitas Abdurrab, 2019)
The development of extensive information technology has encouraged various agencies and schools to apply appropriate information technology, one of which is Tualang 1 Public Middle School. Tualang 1 Public Middle School has implemented a report card management information system since 2015 that is useful to facilitate teachers in managing student report cards. Problems that occur during implementation are errors that occur in inputting values, there are still teachers who do not understand how to input the value of students and tell other teachers to input values ​​into the system, and the server down during the last days of system closure. The purpose of this study was to determine the factors that most influence interest in user behavior based on UTAUT variables which consist of performance expectancy, effort expectancy, social influence, facilitating conditions and moderated by variables of gender, age and experience. The results of this study indicate that the factors that most influence interest in user behavior are effort expectancy of 68.5%, facilitating conditions of 62.7% and performance expectancy of 56.6%. While the moderator gender, age and experience variables affect user interest by 79.0%. As well as the results obtained from the gap between school expectations and user perceptions of -0.9. To overcome GAP the school must conduct evaluation and monitoring regarding the application of information systems for report card management at Tualang 1 Public Middle School.